Impact of inflation on female labor force participation: A panel study on the countries of Indian sub-continent - Bhuiyan, Upoma Rahman (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Applied Economics, 2022.